2013
DOI: 10.1038/hdy.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of two suppressors of OVATE (sov) loci in tomato

Abstract: Tomato fruit shape varies significantly in the cultivated germplasm. To a large extent, this variation can be explained by four genes including OVATE. While most varieties with the OVATE mutation bear elongated fruits, some accessions carry round fruit, suggesting the existence of suppressors of OVATE in the germplasm. We developed three intraspecific F 2 populations with parents that carried the OVATE mutation but differed in fruit shape. We used a bulk segregant analysis approach and genotyped the extreme cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 41 publications
0
48
0
2
Order By: Relevance
“…Results from this study showed that sun enhanced the effect of the ovate in controlling the pear-shaped fruit form. However, whereas sun×ovate resulted in pear-shaped fruit, the effect of ovate is also enhanced into a distinct pear-shaped form by two unrelated suppressor loci, sov1 and sov2 [36]. Further, comparisons among the LA1589 NILs showed that fs8.1 alone did not significantly affect the elongation and size of the fruit.…”
Section: Sun Ovate and Fs81 Appear To Function In Different But Relmentioning
confidence: 75%
“…Results from this study showed that sun enhanced the effect of the ovate in controlling the pear-shaped fruit form. However, whereas sun×ovate resulted in pear-shaped fruit, the effect of ovate is also enhanced into a distinct pear-shaped form by two unrelated suppressor loci, sov1 and sov2 [36]. Further, comparisons among the LA1589 NILs showed that fs8.1 alone did not significantly affect the elongation and size of the fruit.…”
Section: Sun Ovate and Fs81 Appear To Function In Different But Relmentioning
confidence: 75%
“…These second site modifiers have been identified through mutagenesis screens and crosses to different backgrounds. Background-dependent modifiers have been found for developmental pathways as diverse as tomato (Solanum lycopersicum) fruit size and Drosophila (Drosophila melanogaster) bristle number (Gibert et al, 2005;Rodríguez et al, 2013). Maize (Zea mays) is particularly rich for the identification of modifiers because of the high genetic variation among maize inbred lines: to illustrate this point, the coding sequence variation between two maize inbreds is as great as the coding sequence variation between humans and chimpanzees (Pan troglodytes; Buckler et al, 2006), and the noncoding intergenic space is also remarkably variable between inbreds (Brunner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, exogenous auxin clearly elongated the proximal end of the organ leading to pear-shaped fruits resembling the ova-te+sun fruits (Fig. 1B, C) and fruits of the variety Yellow Pear which carries ovate and sov1 (Rodríguez et al 2013. To validate the classification of the auxin-treated fruits with ovate, PCA was performed between the 3 WBA auxintreated and the three NILs using nine fruit shape attributes.…”
Section: Resultsmentioning
confidence: 99%